Pertanggungjawaban Pidana Terhadap Petugas Penyelenggara Program Makan Bergizi Gratis Yang Menyebabkan Keracunan - Asep Rahmat Hidayatulloh; Deny Guntara; Muhamad Abas; Raka Indra Pratama (Fakultas Hukum Universitas Riau, 2026)
This study aims to analyze the legal framework and criminal liability for crimes of negligence committed by officials of the Free Nutritious Meals Program (MBG) that result in food poisoning. The method used is a normative legal approach based on legislation, through a review of the old Criminal Code, Law No. 1 of 2023, and Presidential Regulation No. 115 of 2025. The novelty of this study lies in the analysis of the criminal liability of MBG officers as legal subjects in cases of food poisoning resulting from negligence through a comparison of provisions in the old Criminal Code, the 2023 Criminal Code, and Presidential Regulation No. 115 of 2025, as well as the identification of a legal gap regarding specific regulations for MBG officers. The research findings indicate that poisoning is the result of negligent conduct (culpa), with the level of criminal liability depending on the resulting harm, such as minor injury, serious injury, or death. In the old Criminal Code, Articles 359 and 360 served as the basis, whereas the 2023 Criminal Code regulates this more systematically in Articles 474 and 475, including aggravated penalties for certain professions. The principles of legality and “no punishment without guilt” (geen straf zonder schuld) serve as the primary foundations. This study also identified a regulatory gap regarding specific provisions for MBG officers, highlighting the need for strengthened regulations and oversight.